(untitled) (Research, Society and Development, 2022)
The assessment of the quality of prenatal health care is related to a potential impact on prematurity rates and on the reduction of infant morbidity and mortality rates in the country. Objectives: to relate the results found based on low-risk prenatal policies in primary care; identify, based on the literature, what is being discussed on the topic; building a demonstrative table with the factors involved in the quality of service in low-risk prenatal care found in the literature. Methodology: this is an integrative review of the literature in the light of the theoretical Donabedian. No time frame was included in the search in order not to reduce likely useful content for the search. The databases consulted were: Web of Science, VHL and VHL Public Health, from November 2020 to March 2021 and a survey was made based on the respective queries. Results: the vast majority of articles address criteria that are consistent with professional practice and service protocols. While it is possible to observe that few crossings were made between the three elements proposed by Donabedian, which are structure, process and results. Conclusion: from this study it is possible to understand about the need to expand studies on the subject, mainly in cross-sectional studies, which present proposals for improving the quality of care. Enabling new discussions, in addition to observing the findings from a more complete perspective, since they directly affect the health care that is offered in the different perinatal scenery.